2014
DOI: 10.1111/cas.12497
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor activity of WK88‐1, a novel geldanamycin derivative, in gefitinib‐resistant non‐small cell lung cancers with Met amplification

Abstract: Although epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) have been introduced for the treatment of non-small cell lung cancer (NSCLC), the emergence of secondary T790M mutation in EGFR or amplification of the Met proto-oncogene restrain the clinical success of EGFR-TKIs. Since heat shock protein-90 (Hsp90) stabilizes various oncoproteins including EGFR and c-Met, the inhibition of Hsp90 activity appears as a rational strategy to develop anticancer drugs. Despite preclinical efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Recently, many strategies to overcome EGFR-TKI resistance have been developed in vitro and in vivo, and several agents are undergoing clinical trials (10). Among these agents, HSP90 inhibitors have shown favorable results for sensitization to EGFR-TKIs in NSCLC; the effects of these drugs are mediated by downregulation of HSP90 client proteins including EGFR, MET, Akt, and ErbB3 (35,36). Previously, we demonstrated that ANT2 shRNA downregulated HER2 expression in breast cancer cells, thereby exerting an antitumor effect.…”
Section: Ant2 Expression In Tumor Tissuesmentioning
confidence: 99%
“…Recently, many strategies to overcome EGFR-TKI resistance have been developed in vitro and in vivo, and several agents are undergoing clinical trials (10). Among these agents, HSP90 inhibitors have shown favorable results for sensitization to EGFR-TKIs in NSCLC; the effects of these drugs are mediated by downregulation of HSP90 client proteins including EGFR, MET, Akt, and ErbB3 (35,36). Previously, we demonstrated that ANT2 shRNA downregulated HER2 expression in breast cancer cells, thereby exerting an antitumor effect.…”
Section: Ant2 Expression In Tumor Tissuesmentioning
confidence: 99%
“…This result is consistent with the results of previous research. Furthermore, previous research demonstrated that Met amplification is the primary mechanism used for forming HCC827-GR cells through chronic exposure to gefitinib (38)(39)(40). In future studies, the regulation of the HIF-1 pathway on Met levels in HCC827-GR cells should be observed, and the synergistic effect of YC-1 and gefitinib in HCC827-GR cells should be demonstrated.…”
Section: Discussionmentioning
confidence: 84%
“…Auy922 inhibits growth of EGFR-TKI resistant cell lines by inducing cell programmed death (63) and also displays activity against the gefitinib-resistant sublines with T790M mutation and Met amplification (102). WK88-1 reverses gefitinib resistance by interfering the EGFR or c-Met stability and functions (65). 17-AAG represents a better efficacy for treating nSClC with acquired resistance to EGFR TKIs (103) and the combination of gefitinib and 17-AAG increases nSClC cell growth inhibition (73).…”
Section: Hsp90 and Drug Resistance Of Molecular Targeted Therapymentioning
confidence: 99%
“…Furthermore, Auy922 results in obvious exhaustion of EGFR, Met, HER2 and AKT in nSClC cell lines, giving rise to a reinforcement of apoptosis(64). Hsp90 inhibitor WK88-1 reduces the cell survival of lung cancer cells via reducing the expression of EGFR, ErbB2, ErbB3, Met and Akt(65), and combination treatment of Hsp90 inhibitor ganetespib and erlotinib stabilizes the expression state of EGFR inactivation and disrupts ERK and AKT signaling activity(66). Hsp90 inhibitor 17-DMAG inhibits the growth of Ma-1/HGF cells, H1975 cells and PC-9 cells by downregulating EGFR and Met(67) and exhausting EGFR, AKT, MAPK, Cdk4, and cyclin D1 in EGFR-mutant cell lines(68).…”
mentioning
confidence: 99%